A comparison of the effects of post-mortem aging on breast meat from Cobb 500 and Hubbard ISA broilers - Mello, J. L.M. [UNESP]; Souza, R. A. [UNESP]; Paschoalin, G. C. [UNESP]; Ferrari, F. B. [UNESP]; Machado, B. M. [UNESP]; Giampietro-Ganeco, A. [UNESP]; Souza, P. A. [UNESP]; Borba, H. [UNESP] (CSIRO Publishing, 2018)
We compared the physical and chemical characteristics of the pectoralis major muscle from Cobb 500 and Hubbard ISA broilers and evaluated the effect of aging process for up to 7 days on meat quality. We used breast samples from male Cobb 500 (42 days of age; n ≤ 60) and Hubbard ISA (85 days of age; n ≤ 60) broilers. Twenty samples of each genotype were analysed 4 h post-slaughter (Control group). Another 20 samples of each genotype were aged in an incubator (2 ± 0.5°C) for 3 and for 7 days. Breast fillets were 23% heavier in the Cobb 500 group (306 g vs 248 g; P ≤ 0.0009). Before aging, meat from Hubbard ISA broilers had higher (P < 0.001) water-holding capacity, which promotes the production of less exudate and possibly reduces nutritional losses during storage, which may be beneficial to the poultry industry. Despite being initially less tender, breast meat from Hubbard ISA broilers showed, during the aging process, a reduction (P < 0.05) of shear force (48.46-15.04 N), total collagen amount (6.0-4.8 g/kg) and myofibrillar fragmentation index (150.17-97.42) and had the same (P ≤ 0.134) fat concentration (0.87 g/100 g) as that of breast meat from Cobb 500 broilers (0.93 g/100 g, respectively). Breast meat from Hubbard ISA broilers had a higher (P < 0.001) polyunsaturated fatty acid concentration, especially docosahexaenoic acid, which is beneficial to human health. Aging breast fillets for 3 days at 2°C is sufficient to tenderise the meat without reducing its juiciness, which suggests that the aging process can add value to free-range meat.
Keywords: chicken; free-range poultry; meat quality; PUFA; tenderness